2001
DOI: 10.1111/j.0014-3820.2001.tb01319.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Introgressive Hybridization in the Evolution of the Gila Robusta Complex (Teleostei: Cyprinidae)

Abstract: The extent and impact of introgressive hybridization was examined in the Gila robusta complex of cyprinid fishes using mitochondrial DNA (mtDNA) sequence variation. Lower Colorado River basin populations of G. robusta, G. elegans, and G. cypha exhibited distinct mtDNAs, with only limited introgression of G. elegans into G. cypha. The impact of hybridization was significant in upper Colorado River basin populations; most upper basin fishes sampled exhibited only G. cypha mtDNA haplotypes, with some individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 35 publications
2
41
1
Order By: Relevance
“…This can occur between species that are closely related and between species that are not closely related. Interestingly, introgressive hybridization has long been hypothesized to play an important role in the evolutionary diversification of living organisms whereby lineages have been hypothesized to benefit through the incorporation of new genetic variations (Anderson, 1949;Dowling and Secor, 1997;Gerber et al, 2001). This naturally-occurring process may also have a significant impact in the conservation of species when a rare or endangered species is genetically assimilated by a more common species (DeMarais et al, 1992;Rhymer and Simberloff, 1996;Rieseberg, 1998;Costedoat et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This can occur between species that are closely related and between species that are not closely related. Interestingly, introgressive hybridization has long been hypothesized to play an important role in the evolutionary diversification of living organisms whereby lineages have been hypothesized to benefit through the incorporation of new genetic variations (Anderson, 1949;Dowling and Secor, 1997;Gerber et al, 2001). This naturally-occurring process may also have a significant impact in the conservation of species when a rare or endangered species is genetically assimilated by a more common species (DeMarais et al, 1992;Rhymer and Simberloff, 1996;Rieseberg, 1998;Costedoat et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of sequence variation in humpback chub and roundtail chub (Gila cypha and G. robusta, respectively) from the Colorado River within and above the Grand Canyon indicated that levels of genetic diversity were evenly distributed throughout much of the Colorado River basin (Gerber et al 2001), and analysis of long-term female effective population size of humpback chub from the Grand Canyon was consistent with a stable population (Garrigan et al 2002). In contrast, Douglas et al (2003) found that most of the allelic diversity in populations of flannelmouth sucker was also evenly distributed among populations but levels of nucleotide diversity increased upstream from southwest to northeast.…”
Section: Patterns Of Genetic Diversitymentioning
confidence: 99%
“…The nature of reproductive barriers appears to be dynamic, as reflected by spatial and temporal variation in the degree of reproductive (e.g., Aboim et al 2010). While hybridization appears to be an important component of freshwater fish evolution (Smith 1992;Dowling and Secor 1997;Gerber et al 2001), our understanding of the factors that promote or allow frequent interspecific mating remains limited.…”
Section: Introductionmentioning
confidence: 99%